Ейкозаноїдний контроль загоювання ран у хворих із гнійно-некротичними формами синдрому діабетичної стопи - Свиридов, М. В. (Clinical Endocrinology and Endocrine Surgery, 2010)
The results of surgical treatment of 186 patients with destructive forms of diabetic foot syndrome, classified PEDIS under P1–2E1–2D2–3I2–3 are analyzed. Content of eicosanoids PHE2, LTV4 and PHI2 in blood at various stages of treatment was studied. An imbalance of production prostanoids and leukotriens found that incluenced the efficiency of the use of wound covering, autodermoplasty and speed of wound healing. Eicosanoids may reflect the phasing process and the flow of wound process — transition of inflammation phase in proliferative phase.